Operational Differences in Plant-Based Diet Indices Affect the Ability to Detect Associations with Incident Hypertension in Middle-Aged US Adults. Issue 4 (13th November 2019) - Kim, Hyunju; Rebholz, Casey M; Garcia-Larsen, Vanessa; Steffen, Lyn M; Coresh, Josef; Caulfield, Laura E
ABSTRACT: Background: Several distinct plant-based diet indices (PDIs) have been developed to characterize adherence to plant-based diets. Objective: We contrasted 5 PDIs in a community-based cohort by assessing characteristics of the diet and evaluating whether these PDIs are associated with risk of incident hypertension. Methods: Using FFQ data from adults (45–64 y, n  = 8041) without hypertension at baseline in the Atherosclerosis Risk in Communities (ARIC) Study, we scored participants' diets using the overall PDI (oPDI), healthy PDI (hPDI), less healthy (unhealthy) PDI (uPDI), provegetarian diet index, and PDI from the Rotterdam Study (PDI-Rotterdam). For the oPDI, provegetarian diet, and PDI-Rotterdam, higher intakes of all or selected plant foods received higher scores. For the hPDI, higher intakes of plant foods identified as healthful received higher scores. For the uPDI, higher intakes of less healthy plant foods received higher scores. All indices scored higher intakes of animal foods lower. We examined agreement between indices, and whether scores on these indices were associated with risk of hypertension using Cox proportional hazard models. Results: The PDIs were moderately-to-strongly correlated and largely ranked subjects consistently, except for the uPDI. Over a median follow-up of 13 y, 6044 incident hypertension cases occurred. When adjusted for sociodemographic characteristics, other dietary factors, and health behaviors, the highest compared with the lowest quintile for adherence to the oPDI, hPDI, and provegetarian diet was associated with a 12–16% lower risk of hypertension (all P -trend <0.05). Highest adherence to the uPDI was associated with a 13% higher risk of hypertension, when clinical factors were further adjusted for ( P -trend = 0.03). No significant association was observed with the PDI-Rotterdam. The oPDI, hPDI, and provegetarian diet moderately improved the prediction of hypertension. Conclusions: In middle-aged US adults, despite moderate agreement in ranking subjects across PDIs, operational differences can affect the ability to detect diet–disease associations, such as hypertension.